Analisis Disiplin Pasar Berdasarkan Simpanan Antar Bank Di Indonesia - Yamani, Raisa (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine how much influence Market Discipline (MKD), Total Equity to Total Assets (EQTA), Logarithms of Total Assets (LTA), Net Interset Income (NII), and Obligations (OBG) simultaneously have on SDROA, SDROE, and ZSCORE in 36 banks in Indonesia. The type of research used is descriptive quantitative. The data used is secondary data. This research is a panel data research with panel data regression analysis method conducted with Stata 14. The results showed that the variables Market Discipline (MKD), Total Equity to Total Assets (EQTA), Logarithms of Total Assets (LTA), Net Interset Income (NII), and Obligations (OBG) simultaneously against SDROA, SDROE, and ZSCORE in 36 banks in Indonesia.